Simulation Analysis of Meshing Gear Churning Power Loss based on CFD Method - Shen Lin; Ruan Dengfang; Tu Pan (Jixie chuandong)
It is difficult to determine the gear churning power loss directly by theoretical methods because gear churning power loss has a complex relationship with its influencing factors. Because of the pumping effect of gear meshing,there is a certain difference between single gear churning and meshing gears churning. However,the existing formulas for calculating the churning power loss are mostly aimed at single gear churning power loss and its application is very limited. The CFD software FLUENT is used to simulate the gear churning during the no-load of a pair of meshing gears. The calculation results are compared with the experimental results. The influence of gear rotation direction and gear ratio on the gear churning power loss is analyzed. The difference of the oil loss between spur gear and helical gear is also compared. The results show that the simulation results are close to those of the test results and the simulation method can accurately predict the power loss of the gear meshing gear. The gear rotation direction,gear ratio and helix angle have great effects on the churning power loss of the gear pair.